Surface plasmon polariton modulator based on electro-optic polymer - Chen Jian-Jun; Li Zhi; Zhang Jia-Sen; Qi-Huang, Gong (Acta Physica Sinica, 2008)
A simple, high efficiency and mini-sized surface plasmon polariton (SPP) modulator based on electro-optic polymer is proposed. The modulator is constructed by metallic stripes of Mach-Zender (M-Z) interferometric structure and with electro-optic polymer surrounding the stripes. The reflectivity index of the eleetro-optic polymer is modulated when the modulating voltage is applied to the two arms of the M-Z interferometer. Through the M-Z interferometer, the modulation of the reflectivity index can be transferred into the modulation of the SPP intensity. By calculating the electric field near the metallic stripes and taking the distribution of SPP field into account, the working principle of the SPP modulator is demonstrated in detail and the half-wave modulating voltage is evaluated as 2.8 V.